EXPERT RISK ASSESSMENT OF FMD INTRODUCTION TO THE RUSSIAN FEDERATION FROM INFECTED COUNTRIES - V. M. Gulenkin; A. K. Karaulov; D. A. Lozovoy; V. M. Zakharov (Ветеринария сегодня)
Predictive assessment of possible risks of FMD introduction from neighboring countries to the territory of eight RF Federal Districts was presented. The risk quantitative parameters were determined by experts, specialists in the field of FMD epidemiology. To implement the expert survey method most significant routes of infection introduction to the RF were determined. The experts performed FMD introduction risk assessment for each federal district and determined its score. As a result of statistical analysis the greatest probability was determined for the Far-Eastern Federal District. The North Caucasus and Siberian Federal Okrugs demonstrate lower probability. Basing on the obtained data the major routes of FMD introduction to the territory of the country were determined. Preventive vaccination of susceptible animal population is carried out in order to prevent FMD occurrence and spread in the zones at risk of its introduction. It is aimed at FMD outbreak prevention in the specified RF Subjects by inducing protective immunity in at least 81% of immunized cattle and at least 95% of immunized pigs.